PELAKSANAAN TERAPI OKUPASI DAN IMPLIKASI DALAM PEMBELAJARAN PADA ANAK CEREBRAL PALSYJENIS SPASTIK DI SDLB NEGERI PATRANG JEMBER - Olivia Nur Isnaini; Wiwik Dwi Hastuti (Universitas Negeri Malang, 2014)
The objective of this study were to describe: (1) the implementation of the occupation therapy for the spastic Cerebral Palsy children (SCPC) in SDLB Negeri Patrang related to the design, implementation, and evaluation; (2) the implementation of therapy in the classroom (3) the obstacles of th therapy implementation; (4) the solutions of the obstacle during the implementation of occupation therapy. This research type was case study with qualitative approach. Data collection technique was observation, interview, and documentation technique. The research was conducted in SDLB Negeri Patrang Jember. The data sources were of the class teacher in the 3rd-D1 Grade, Cerebral Palsy Spastic student, and many documents that made as secondary source from the researcher. The research result showed that: (1) the implementation of occupation therapy for the spastic Cerebral Palsy children (SCPC) provided in SDLB Negeri (State Special Elementary School) Patrang Jember has not been appropriate with the planning made in the therapy design arrangement, (2) the occupation therapy was implemented with unqualified equipment, and the therapist was often absent, (3) the therapy evaluation was applied as the coordination training and score giving. The obstacle faced in this research was need time and too long design arrangement, therapist rarely come to the school. Thus, therapy implementation must be delayed and cannot run as what has been scheduled. Besides that, the obstacle also came from the parent giving less support for therapy implementation in school, and now the facility of the school physical therapy was inadequate. Thus, the therapy room still cannot be arranged well and tidy. Tujuan penelitian ini: (1) Untuk mendeskripsikan bagaimana pelaksanaan terapi okupasi pada anak CP Spastik di SDLB Negeri Patrang terkait perencanaan, pelaksanaan, dan evaluasinya, (2) Untuk mendeskripsikan bagaimana penerapan terapi okupasi didalam kelas (3) Untuk mendeskripsikan kendala yang dijumpai dalam pelaksanaan terapi, (4) Untuk mendeskripsikan bagaimana solusi dalam mengatasi kendala yang dijumpai selama pelaksanaan terapi okupasi.Hasil penelitian menunjukkan bahwa pelaksanaan Terapi Okupasi pada anak CP Spastik di SDLB Negeri Patrang belum sesuai perencanaan yang dibuat dalam penyusunan perencanaan terapi, pelaksanaan terapi okupasi dengan peralatan seadanya dan seringnya terapis tidak hadir, serta evaluasi terapi yang dilakukan berupa latihan koordinasi dan pemberian skor. Kendala yang dijumpai yaitu penyusunan perencanaan yang terlalu lama dan membutuhkan waktu, terapis jarang datang kesekolah sehingga pelaksanaan terapi harus ditunda dan tidak berjalan sesuai yang dijadwalkan. Selain itu, kendala lain juga datang dari pihak orang tua yang kurang mendukung pelaksanaan terapi disekolah, serta saat ini untuk fisik sarana sekolah masih kurang sempurna, sehingga ruang terapi masih belum bisa tertata dengan baik dan rapi